2011
DOI: 10.1016/j.jjcc.2010.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP2C19 polymorphism on residual platelet reactivity in patients with coronary heart disease during antiplatelet therapy

Abstract: CYP2C19 polymorphism may be associated with high residual platelet reactivity and the occurrence of cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 25 publications
(29 reference statements)
5
63
0
1
Order By: Relevance
“…CYP2C19 has been reported to contain several polymorphisms which are more frequent in Asian populations, particularly in the Japanese population. 3,8) Indeed, in Japanese populations, 37% are EMs, 44% are IMs, and 19% are PMs.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2C19 has been reported to contain several polymorphisms which are more frequent in Asian populations, particularly in the Japanese population. 3,8) Indeed, in Japanese populations, 37% are EMs, 44% are IMs, and 19% are PMs.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that 56% of Japanese patients have CYP2C19-induced metabolism abnormalities. 21) Based on these findings, Watanabe, et al pointed out that there is a risk associated with administering DAPT to all TAVI patients. In a meta-analysis to study whether P2Y12 reactivity units (PRU) can predict the prognosis, 3059 patients undergoing PCI were analyzed in 6 studies, and a significantly high incidence of complications due to MI or stent thrombosis was reported for patients with PRU ≧ 230.…”
Section: Article P190mentioning
confidence: 99%
“…Five meta-analyses did not include conference abstracts, 5,25,[28][29][30] and all but one of the metaanalyses left out data from one or more full articles that were included in other meta-analyses (Supplementary Table S1 and Supplementary Appendix S1 online). [34][35][36][37][38][39][40][41] For example, the post hoc genetic analysis of the ACTIVE-A trial was included in only two of the seven meta-analyses that did their literature searches after the publication of the trial, 6,24 and one meta-analysis had limited the inclusion to only primary studies with a follow-up time of 6-12 months.…”
Section: -30mentioning
confidence: 99%